1998
DOI: 10.1177/002580249803800312
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Volunteer Appropriate Adult Scheme

Abstract: This paper discusses the first evaluation to be undertaken of a volunteer Appropriate Adult scheme for mentally vulnerable adults. Southampton MIND was granted funding by the Mental Health Foundation to implement a volunteer Appropriate Adult scheme which began in April 1994 and lasted for two years. The Mental Health Foundation required an evaluation from an independent organization, the implications of which are examined here against the background of previous research conducted by the authors on the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…4 In terms of availability, our stereotypical volunteer, more likely than not to be in work, may in fact not be so reliable. Most calls for appropriate adult assistance for mentally disordered suspects come during working hours (Nemitz and Bean, 1998), and given the high correlation between youth offending and truancy (Hyder, 1989) and school exclusion (Bratby, 1998), there is no reason to think the situation should greatly differ for young suspects. If non-availability translates into delay for the young suspect awaiting assistance before interview, it becomes problematic and dangerous as delay inevitably places further pressure on already stressed young shoulders, increasing the risk of unsafe confessions.…”
Section: Safeguarding the Interests Of The Young Suspect: Questioningmentioning
confidence: 99%
“…4 In terms of availability, our stereotypical volunteer, more likely than not to be in work, may in fact not be so reliable. Most calls for appropriate adult assistance for mentally disordered suspects come during working hours (Nemitz and Bean, 1998), and given the high correlation between youth offending and truancy (Hyder, 1989) and school exclusion (Bratby, 1998), there is no reason to think the situation should greatly differ for young suspects. If non-availability translates into delay for the young suspect awaiting assistance before interview, it becomes problematic and dangerous as delay inevitably places further pressure on already stressed young shoulders, increasing the risk of unsafe confessions.…”
Section: Safeguarding the Interests Of The Young Suspect: Questioningmentioning
confidence: 99%
“…Immediate access to a police surgeon may be dif cult, especially in large rural areas. In the intervening period, the detainee, about whose condition the custody of cer is concerned, is denied access to an appropriate adult (Nemitz and Bean, 1998). MIND's report into the operation of section 136 of the Mental Health Act 1983 felt that the advice provided to the Police by police surgeons added little to what was already known.…”
Section: Identifying the Need For An Appropriate Adultmentioning
confidence: 99%
“…Police of cers reported that assessments were generally very brief (MIND, 1991: 156). In their study of the Southampton MIND voluntary scheme, Nemitz and Bean (1998) gained the impression that police surgeons link tness to be interviewed with not being sectionable under the Mental Health Act 1983. Norfolk (1997) seeks to identify the circumstances in which doctors should certify unfitness to plead and those where the detainee is fit for interview, but should be accompanied by an appropriate adult.…”
Section: Identifying the Need For An Appropriate Adultmentioning
confidence: 99%
See 2 more Smart Citations